Diagnostic Imaging Fundamentals: Brain Vascular Pathology - Erwin Xia; Efrain Lee-Diaz; Miguel Trelles de Belaunde; Jorge Lee Diaz (Association of American Medical Colleges, 2017)
Introduction This module was created to supplement the traditional learning methods that senior medical students, first-year radiology residents, and residents in other specialties employ to learn the fundamentals of radiologic image interpretation. It is part of an ongoing project entitled Diagnostic Imaging Fundamentals (DIF), with each module covering a unique topic. This module covers brain vascular anatomy, common imaging modalities, and imaging characteristics of brain vascular pathologies. Methods This module has been designed for team-based learning and consists of advance-preparation reading material, in-class individual and group readiness assurance tests, and a group application exercise. Students are evaluated both individually and as groups. These DIF modules are designed primarily for group learning and are well suited for the academic setting. Results The feedback we received from first-year radiology residents was 100% positive, and the most frequent remark used by learners in their comments was "very helpful." Our limited feedback suggests that the level of material is appropriate for trainees at or above their final year of medical school. Discussion We are confident that this module will benefit students and residents who are eager to learn the fundamentals of brain vascular imaging and will serve as a useful adjunct to traditional methods of learning. We believe the module's application of team-based learning can act as a model for collaborative learning in a traditionally didactic learning environment. Future work will include expanding use of the module to larger groups of radiology residents, medical students, and residents in other specialties.